Mixed-integer nonlinear programming models for optimal design of reliable chemical plants - Ye, Yixin; Grossmann, Ignacio E.; Pinto, Jose M. (Computers & chemical engineering, 2018)
•Serial structure with parallel equal/unequal equipment is assumed with given reliability.•Convex MINLP model is proposed for maximizing availability and minimizing cost.•Nonconvex MINLP model is proposed for maximizing net profit based on availability.•Application of models is illustrated with small examples and in the synthesis of flowsheets. Motivated by reliability/availability concerns in chemical plants, this paper proposes MINLP models to determine the optimal selection of parallel units considering the trade-off between availability and cost. Assuming an underlying serial structure for availability, we consider first a case where the system transitions between available and unavailable states, and second the case with an intermediate state at half capacity. Two non-convex MINLP models maximizing net profit are introduced for the two cases. In addition, a bi-criterion MINLP model is proposed to maximize availability and to minimize cost for the first case. It is shown that the corresponding epsilon-constrained model, where the availability is maximized subject to parametrically varying upper bound of the cost, can be reformulated as a convex MINLP. Availability is also incorporated in the superstructure optimization of process flowsheets. The performances of the proposed models are illustrated with a methanol synthesis and a toluene hydrodealkylation process.